UNSUR-UNSUR LITURGIS DALAM KEHIDUPAN GEREJA YERUSALEM PADA PERIODE TUJUH ABAD PERTAMA - Rahawarin, Bernard A. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
Jerusalem is a most important city in connection with the original ecclesiastical community. Though at first the city could establish a metropolitan position in terms of hierarchical ecclesiastical structure like the Churches of Antioch (Syria), Alexandria and Rome, nevertheless in matters of liturgy, the Church of Jerusalem produced a lot of Christian liturgical practices, which are at the base of liturgical practice in the modern Church. Knowledge of liturgical basics in the Church of Jerusalem during the first seven centuries may be of assistance to us to better comprehend genuine liturgy, which is continued up to now. Thus we can lessen the loss of orientation in any liturgical inculturation effort. Moreover, we will be helped to remind ourselves on the importance of strategical renewal while returning to basics in order to stress again our identity and orientation of faith, which is mirrored in our liturgical practice.